Synthesis and in vitro antiproliferative evaluation of D-secooxime derivatives of 13β- and 13α-estrone - Mernyák Erzsébet (STEROIDS, 2014)
Abstract D-Secooximes were synthesized from the D-secoaldehydes in the 13β- and 13α-estrone series. The oximes were modified at three sites in the molecule: the oxime function was transformed into an oxime ether, oxime ester or nitrile group, the propenyl side-chain was saturated and the 3-benzyl ether was removed in order to obtain a phenolic hydroxy function. Triazoles were formed via Cu(I)-catalysed azide-alkyne cycloaddition (CuAAC) from 3-(prop-2-yniloxy)-D-secooximes and benzylazides. All the products were evaluated in vitro by means of MTT assays for antiproliferative activity against a panel of human adherent cell lines (HeLa, MCF-7, A2780 and A431). Some of them exhibited activities with submicromolar IC50 values, better than that of the reference agent cisplatin. The structural modifications led to significant differences in the cytostatic properties. Flow cytometry indicated that one of the most potent agents resulted in a cell cycle blockade.